Польський національний рух у Правобережній Україні: регіональна специфіка - Громакова, Н.Ю. (Історичний архів. Наукові студії, 2015)
У статті досліджено особливості розвитку польського національного руху в Правобережній Україні у другій половині ХІХ ст. Національний рух поляків у цей період представляє собою складний історичний феномен, що вплинув на трансформацію суспільно-політичного простору українських земель. Автор дійшов висновку, що формування нового способу мислення власного соціально-історичного простору учасниками польського національного руху спричинилося до перетворення регіону на арену запеклої боротьби російського, польського й українського національних проектів. В статье рассматриваются особенности развития польского национального движения в Правобережной Украине во второй половине ХІХ в. Национальное движение поляков в этот период представляет собой сложный исторический феномен, повлиявший на трансформацию общественно-политического пространства в украинских землях. Автор резюмирует, что формирование нового способа мышления участниками польского национального движения своего социально-исторического пространства способствовало превращению региона в арену жестокой борьбы российского, польского и украинского национальных проектов. The article is devoted to studying problems of the Polish National Movement development on the Right-Bank Ukraine during the second-half of the XIXth century. The National Movement of the Poles at that period was the complex historical phenomenon, that influenced on the transformation of the socio-political spaciousness of the Ukrainian lands. The author by the analyze of the scientific discourse was defined the content and essence of the
concept «the Polish National Movement» at the context of the genesis of nationalisms in the Central-East Europe during the modern period. The author emphasizes, that the spreading of the Polish National Movement on the Right-Bank Ukraine was occurring under circumstances of competition’s struggle with the Russian imperial nation building, moreover, the participants of the both two movements were considered the regional non-poles exclusively as part of their own national identity.
The second-half of the XIXth century was the period of the transformation of the ideology’s origins and the spreading new forms and methods of the practical activity of the Polish National Movement’s participants. The conspiracy and the rebellion were replaced with the «organic work». It meant to put into usual practice the modern educational and economic forms of activity as the basis of the future Polish state’s rebirth.
The author came to the conclusion, that the genesis of the modern Polish nation was promoting to the forming the new way of mind of their own socio-historical space by the participants of the national movement. The traditional regional-representative’s patriotism by the «Rzeczpospolita»‘s period was replaced by the new conception of the national state. The fundamental idea of this conception was the idea of the national unity and the granting political rights to all Poles. However the polish territorial claims to the non-polish lands former «Rzeczpospolita», specifically the Right-Bank Ukraine, caused the emphasizing of the conflict with the Russian nationalism’s adepts and the participants of the Ukrainian National Movement. This opposition became the important factor of the socio-political living in the region, that transformed into the area of the fierce fighting of Russian, Polish and Ukrainian national projects.